2022
DOI: 10.5334/aogh.3663
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Adaptation of an International Exchange Program in Medical Education

Abstract: Medical education has drastically transformed during the COVID-19 pandemic. Measures such as adopting telemedicine visits, minimizing the number of trainees on service, discontinuing external rotations, and converting in-person to online didactics have been broadly and swiftly implemented. While these innovations have promoted greater interconnectivity amongst institutions and made continuing medical education possible, international exchange programs in medical education are still largely disrupted. In respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…In 2020, the NINDS began a health equity strategic planning process that has recently culminated in 18 high‐level recommendations, including for the training of scientists from historically underrepresented backgrounds 70 . Academic institutions are also developing exchange programs to deliberately enhance the cross‐cultural skills of their faculty and trainees 71 . Because transformative education is key for liberation, similar efforts could be considered by all constituents of the translational research cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, the NINDS began a health equity strategic planning process that has recently culminated in 18 high‐level recommendations, including for the training of scientists from historically underrepresented backgrounds 70 . Academic institutions are also developing exchange programs to deliberately enhance the cross‐cultural skills of their faculty and trainees 71 . Because transformative education is key for liberation, similar efforts could be considered by all constituents of the translational research cycle.…”
Section: Resultsmentioning
confidence: 99%
“…70 Academic institutions are also developing exchange programs to deliberately enhance the cross-cultural skills of their faculty and trainees. 71 Because transformative education is key for liberation, similar efforts could be considered by all constituents of the translational research cycle.…”
Section: Strategy 5: Study Sdohs and Lived Experiencesmentioning
confidence: 99%
“…When the feasible online program is planned, some challenges and advantages should be discussed. In an online program, one of the biggest issues is the network environment [ 7 , 26 ]. Although the internet environment in our case was mostly stable and had a good connection, maintaining stability may be a significant problem depending on the area and socio-economic factors [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the medical educational field, there are a few reports of online international programs such as virtually visiting a medical institution in another country [ 4 , 5 ]. However, there are few reports of international exchange programs in which students participate from two or more universities and conduct activities together for several weeks [ 6 , 7 ]. To the best of our knowledge, there is no report promoting a program with interactive communication for a period of several months.…”
Section: Introductionmentioning
confidence: 99%
“…In the medical education field, there are several reports of online programs, such as virtually visiting medical institutions in other countries during travel restrictions due to the pandemic. [5][6][7] There are some reports of international exchange programs in which students from two or more universities participate in activities together for several weeks. [8][9][10] These studies reported that well-organized and structural virtual programs could contribute to fostering globally competent medical professional students and give the opportunity for international experience to students from various backgrounds.…”
Section: Introductionmentioning
confidence: 99%